Mott transition and magnetic collapse in iron-bearing compounds under high pressure. Issue 2 (3rd April 2017) - Leonov, I.; Greenberg, E.; Belov, M.P.; Rozenberg, G.Kh.; Abrikosov, I.A.
ABSTRACT: We discuss the electronic, magnetic, and related structural transitions in the iron-based Mott insulators under high pressures relevant to the Earth's lower mantle conditions. The paper focuses on the above-mentioned topics based primarily on our theoretical analysis and various experimental studies employing synchrotron X-ray diffraction, 57 Fe Mössbauer spectroscopy, and electrical transport measurements. We review the main theoretical tools employed for the analysis of the properties of materials with strongly interacting electrons and discuss the problems of theoretical description of such systems. In particular, we discuss a state-of-the-art method for calculating the electronic structure of strongly correlated materials, the DFT + DMFT method, which merges standard band-structure techniques (DFT) with dynamical mean-field theory of correlated electrons (DMFT). We employ this method to study the pressure-induced magnetic collapse in Mott insulators, such as wüstite (FeO), magnesiowüstite (Fe 1 − x Mg x )O ( x =0.25 and 0.75) and goethite (FeOOH), and explore the consequences of the magnetic collapse for the electronic structure and phase stability of these materials. We show that the paramagnetic cubic B 1 -structured FeO and (Fe, Mg)O and distorted orthorhombic ( Pnma ) FeOOH exhibit upon compression a high- to low-spin (HS-LS) transition, which is accompanied by a simultaneous collapse of local moments. However, the HS-LS transition is found to have different consequences for the electronic properties of these compounds. For FeO and (Fe 0.75 Mg 0.25 )O, the transition is found to be accompanied by a Mott insulator-to-metal phase transition. In contrast to that, both (Fe 0.25 Mg 0.75 )O and FeOOH remain insulating up to the highest studied pressures, indicating that a Mott insulator to band insulator phase transition takes place. Our combined theoretical and experimental studies indicate a crossover between localized to itinerant moment behavior to accompany magnetic collapse of Fe ions.